Examination of suitability of factor endowment theory with the reflection on transportation cost in international business - K, Manjuntha; Patil, Bheemanagouda (Journal of Management and Science, 2013)
International Business is a device which provides a support of convenience of exchanging goods or services or both between two or more countries. More prominently in a condition, one good is available abundant in one country and in the identical point of time there is a dearth and much demand from another country for the same or similar goods. During 18th and 19th century a number of international trade theories came into force with the aim of identifying course of action for smooth carrying of business by countries through export and import. Factor Endowment Theory is one of international trade theories focuses on effective international business with the optimum utilization of factors of production.